2012
DOI: 10.1038/cddis.2012.167
|View full text |Cite
|
Sign up to set email alerts
|

JNK2 is activated during ER stress and promotes cell survival

Abstract: Adaptation to endoplasmic reticulum (ER) stress relies on activation of the unfolded protein response (UPR) and induction of autophagy. Indeed, cells die if ER stress is not countered by the UPR. Here we show in U937 cells that the ER stressors tunicamycin and thapsigargin cause increased expression of c-Jun N-terminal kinase 2 (JNK2), which allows regulation of the UPR, whose silencing or pharmacological inhibition delays BiP (immunoglobulin heavy-chain binding protein) upregulation, and causes earlier and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 42 publications
5
68
0
2
Order By: Relevance
“…B95-8 cells transfected with pEGFP-LC3 were treated with TPA (20 ng/ml) and sodium butyrate (3 mM) for 24 h, washed in PBS solution, and incubated with LysoTracker red DND-99 (100 nM) (L7528; Life Technologies), a fluorescent acidotropic probe with high selectivity for acidic organelles, for 30 min at room temperature (10). After several washings with PBS solution, the lysosomes were analyzed using an Apotome Axio Observer Z1 inverted microscope (Zeiss) equipped with an AxioCam MRM Rev.3 at ϫ40 magnification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B95-8 cells transfected with pEGFP-LC3 were treated with TPA (20 ng/ml) and sodium butyrate (3 mM) for 24 h, washed in PBS solution, and incubated with LysoTracker red DND-99 (100 nM) (L7528; Life Technologies), a fluorescent acidotropic probe with high selectivity for acidic organelles, for 30 min at room temperature (10). After several washings with PBS solution, the lysosomes were analyzed using an Apotome Axio Observer Z1 inverted microscope (Zeiss) equipped with an AxioCam MRM Rev.3 at ϫ40 magnification.…”
Section: Methodsmentioning
confidence: 99%
“…The UPR activation by the endoplasmic reticulum (ER) stressor TG can trigger EBV viral replication in B lymphoblastoid cells (LCL) as well (9). TG is known to activate autophagy, as a prosurvival mechanism, during ER stress (10). However, the impact of autophagy on the reactivation of EBV from latency has not been investigated yet.…”
mentioning
confidence: 99%
“…JNK is a set of enzymes activated (dual phosphorylated) by MAPK kinases MKK4 and MKK7, in response to a variety of stress signals such as UV irradiation, chemotherapy damage, osmotic stress, hypoxia/anoxia, and hyperthermia (7). The JNK family consists of JNK1, JNK2, and JNK3, each with multiple isoforms generated through alternative splicing.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (29) reported that NAG7 promoted human NPC invasion and had a potential role in promoting NPC invasion via the regulation of estrogen receptor α and the H-Ras/p-c-Raf and JNK2/activator protein 1/matrix metalloproteinase 1 signaling pathways. Raciti et al (30) reported that JNK2 prevented the accumulation of the acidic compartment in U937 cells undergoing autophagic flux and contributed to the survival of stressed cells (30). JNK1/2 deficiency has also been shown to increase branching morphogenesis and lead to defects in the clearance of lumenal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%